Assessment of the Guide Course Training Programme and Acquired Competences (Laisvalaikio tyrimai, 2023)
Relevance. The guide is the organiser and presenter of the excursion process. It is a person who provides tourists with information about the museums, galleries, natural, cultural, scientific exhibitions or other attractions that are visited. The profession of a guide is very important because the professionalism of the guides largely depends on what impression tourists will make about the country or city they visited. Guides must have the necessary talents and knowledge, these competencies are acquired by guides in guide training courses consisting of 9 subjects taught. They apply the competencies acquired in the courses when working with tourists, and practice develops their personal qualities, which, as the guides say, are important.Keywords: guide courses, guide course training program, competencies.